PENDEKATAN PEMBELAJARAN BERDASARKAN MASALAH (PBM) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 014 PUTAT KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Edi Mohd.Zen Edi Mohd.Zen; Damanhuri Daud Damanhuri Daud; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Background problem in this study is the result of social studies fourth grade students of SD Negeri 014 Putat still relatively low or insufficient standards set KKM school is 65 students who achieve KKM only 8 people or 40% in the classical style. For research held pembelajarn learning approach based problems (PBM). Rerumusan issue: whether the approach can increase the problem pembelajran based learning outcomes IPS Elementary School fourth grade students Putat 014 Land District of White? This study aims to improve learning outcomes IPS Elementary School fourth grade students Putat 014 Land District of White through problem-based learning approach. This research is a form of action research (PTK). The subjects were fourth grade students of SD Negeri 014 Putat ajran second semester of 2013/2014 the number of 20 students consisting of 8 students and 12 students. From the data analysis the percentage increase in the activity of the first cycle of the first meeting of Teachers 60% second meeting increased 70% has increased to the first meeting of the second cycle to 80% and increased again at the second meeting of the second cycle to 95%. While the percentage of student activity in the first cycle the first meeting 35% increase in the second meeting to 60% and increased again at the second meeting of the second cycle to 70% and then increased student learning outcomes from the first cycle to the base score is an average of 60.25 to 71 with a percentage increase of 17.84% and an increase in learning outcomes from the first cycle to the second cycle of the average-rata71 be 81.5 with a percentage increase of 14.84%. The results of the study in fourth grade 014 State Putat prove that Problem Based Learning Approach can improve learning outcomes IPS Elementary School fourth grade students Putat 014 White Land District of Rokan Hilir. Keywords: Problem Based Learning Approach (PBM), Learning Outcome